Reactions of spiked and open chain cluster hydrides with Au complexes: Skeletal rearrangement and crystal structures of heterometallic clusters [Au2Ru4(CO)12(μ4-PCF 3)(PMe3)2] and [Au2Ru4(CO)12(μ3-PCF 3)2(PPh3)2] - Ang, H.-G. (2014)
Journal of Organometallic Chemistry